Genetic amplification of the vascular endothelial growth factor (VEGF) pathway genes, including VEGFA, in human osteosarcoma - Jilong Yang; Da Yang; Yan Sun; Baocun Sun; Guowen Wang; Jonathan C. Trent; Dejka M. Araujo; Kexin Chen; Wei Zhang (2011)
Abstract BACKGROUND: Osteosarcoma is the most common primary tumor of bone. It is a highly vascular and extremely destructive malignancy that mainly affects children and young adults. The authors conducted microarray‐based comparative genomic hybridization (aCGH) and pathway analyses to gain a systemic view of pathway alterations in the genetically altered genes. METHODS: Recurrent amplified and deleted genes that were detected by aCGH were subjected to an analysis based on the Kyoto Encyclopedia of Genes and Genomes to identify the altered pathways. Among the enriched pathways, vascular endothelial growth factor (VEGF) pathway genes collectively were amplified, and alterations of this pathway were validated by fluorescence in situ hybridization (FISH) and immunohistochemistry analyses in 58 formalin‐fixed, paraffin‐embedded osteosarcoma archival tissues that had clinical follow‐up information. RESULTS: The pathway enrichment analyses of the aCGH data revealed that VEGF pathway genes, including the VEGFA gene itself, were amplified significantly in osteosarcoma. Genetic amplification of the VEGFA gene, both focally and in larger fragment, was validated by FISH analysis. It is noteworthy that amplification of the VEGFA gene and elevated expression of the VEGFA protein were associated significantly with microvascular density and adverse tumor‐free survival in patients with osteosarcoma. CONCLUSIONS: The authors report for the first time that VEGF pathway genes, including the VEGFA gene, are amplified in osteosarcoma. Amplification of the VEGFA gene is not only an important mechanism for elevated VEGFA protein expression but also is a poor prognostic factor for tumor‐free survival. Combined classification of VEGFA gene amplification and positive VEGFA protein expression may provide a more accurate stratification method of selecting anti‐VEGF therapy for patients with osteosarcoma. Cancer 2011;. © 2011 American Cancer Society.